REPRESENTASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MELALUI PEMBELAJARAN MEMBATIK - Ghufronudin Ghufronudin; Ahmad Zuber; Argyo Demartoto (Jurnal Analisa Sosiologi, 2017)
Globalization outcome on the decline of the student’s love at local wisdom so that, student’s lack understanding to the significance of the batik’s existence as a heritage which full of life’s wisdom value. The aim of this research is to analyze the character education based on local wisdom representationthrough making batik at Batik 2 Senior High School, Surakarta.The analysis unit in this qualitative research with case study approach is stakeholders of Batik 2 Senior High School, Surakarta that been selected by purposeive sampling. Data collecting by observation, in-depth interview and documentation. Data validation with source triangulation the these data being analyzed by interactive model.The result of this resarch is show that, through making batik lessons in the school can achieve the balance on student’s between their consience, supra-ritual and intellectual related conected with God through philosophy and symbol of batik. Making batik lessons which carried out in the classical way through theory as well as pracctice bring positive impact for student’s character building that fit local wisdom values.Keywords:Batik, Local Wisdom, Character Building, Representation. AbstrakGlobalisasi berdampak pada menurunnya kecintaan siswa pada kearifan lokal sehingga siswa kurang memahami makna eksistensi batik sebagai warisan budaya yang kaya nilai-nilai kebijaksanaan hidup.Penelitian ini bertujuan untuk menganalisis representasi pendidikan karakter berbasis kearifan lokal melalui pembelajaran membatikdi SMA Batik 2 Surakarta.Unit analisis penelitian kualitatif dengan pendekatanstudi kasus ini adalah stakeholders SMA Batik 2 Surakarta yang dipilih dengan purposive sampling.Teknik pengumpulan data dengan observasi, wawancara mendalam dan dokumentasi.Validitas data dengan triangulasi sumber lalu dianalisis dengan modelinteraktif.Hasil penelitian menunjukkan bahwa melalui pembelajaran membatik di sekolah dapat tercapai keseimbangan hati nurani, supra-ritual, dan intelektualitas siswa berkaitan dengan Tuhan melalui kandungan nilai falsafah dalam simbol batik.Pembelajaran membatik yang dilakukan secara klasikal melalui teori maupun praktik berdampak positif bagi pembentukan karakter siswasesuai dengan nilai-nilai kearifan lokal.Kata Kunci: Batik,Kearifan Lokal, Pendidikan Karakter, Representasi.